ECONOMIC BURDEN OF HYPERCHOLESTEROLEMIA IN THE RUSSIAN FEDERATION - A. V. Kontsevaya (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2018)
Background. The prevalence of hypercholesterolemia (HCE) is quite high in the Russian Federation (RF), and it is associated with clinical consequences and with potential economic impact. Impact includes not only cost of its correction, but also the cost of treatment of diseases and complications, as well as the deficiency of the gross domestic product (GDP).Aim. Evaluation of economic impact due to HCE in the Russian population, including direct expenditures of the Health Care System as well as nondirect impact in common economy.Material and methods. Prevalence of HCE in the RF was identified based on local published studies. Local statistical data (2016) on cardio-vascular diseases (CVDs), including Ischemic Heart Disease (IHD), Myocardial Infarction and cerebral-vascular disease were included in the analysis. Population Attributive Risk (PAR) of HCE in CVDs has been extrapolated on all Russian population. Official statistics, parameters of Govern Guarantees Program of Free Medical Aid were used for modelling of direct and non-direct components of economic impact. Total amount of premature deaths with calculation of years of potential life lost until life expectation at 72 years was calculated. Economic impact due to premature CVDs mortality in economic activity age with consideration on ratio of employment have included GDP lost. Calculation of GDP lost also included monetary impact based on number of disability CVDs patients multiplied on GDP per capita in disability group.Results. Visits to policlinics of patients with CVDs and HCE had a first place among all calls for medical aid. In the same time, hospitalization required in higher expenditures (outpatients cost treatment expenditures were 2.43 billion RUR, in-patients treatment – 18.21 billion RUR). IHD with HCE was most expensive for direct expenditures in comparison with other CVD groups: more than 28.9 billion RUR per year, and with direct non-medical expenditures of 29.3 billion RUR in total. Years of potential life lost in economic active age were one million in total, 1.29 trillion RUR per year mostly due to indirect expenditures due to premature deaths in economy activity age (99% of impact). Total Economic impact due to HCE in the Russian population for all HCE are estimated as 1.295 trillion RUR.Conclusion. Total economic impact due to HCE in the RF is 1.5% of GDP (2016), 1.295 trillion RUR. Direct expenditures included Health Care System expenses; disability covering had 2.3% only. Main part of impact is economic lost due to premature mortality and decrease of labor productivity. HCE patients control at target levels with help of healthy lifestyle and adequate pharmaceutical therapy can decrease economic impact.